NILAI ADAPTIF-REFLEKTIF DALAM SINDIR-KIAS SEBAGAI WUJUD DINAMIKA KEBUDAYAAN BAHASA MINANGKABAU - Putra, Andri Azis (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2017)
Language is a vital issue in a culture. Minangkabau as a devoted clan to their oral tradition has a unique linguistic dynamics. Through the